ENHANCING SELF-REGULATED LEARNING THROUGH A CULTURE-INTEGRATED STEM FLIPPED CLASSROOM APPROACH - Hairul Saleh; Dian Nopitasari; Westi Bilda; Ahmad Fadillah (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This study was prompted by the challenge of low student autonomy in traditional education and the urgent need to foster self-regulated learning (SRL) through contextually relevant methods. It examined the effectiveness of a Culture-Integrated STEM–Flipped Classroom model in improving students’ SRL. Using a quasi-experimental, pretest-posttest non-equivalent control group design, students from intact classes were assigned to an experimental group receiving the culture-integrated STEM–Flipped intervention and a control group receiving conventional instruction. SRL was measured before and after the intervention, and improvement was evaluated through gain score analysis. Results showed that the experimental group achieved a substantially higher gain (M=13.28) than the control group (M=5.44). The magnitude of the intervention effect, calculated using Cohen’s d, was d=0.88, indicating a large effect. These findings demonstrate that integrating cultural values within a STEM-based flipped learning environment can significantly enhance students’ ability to plan, monitor, and regulate their learning processes. The study concludes that combining culturally meaningful learning contexts with structured pre-class preparation and active in-class STEM problem solving provides a powerful approach for strengthening SRL.